In vivo evaluation of an elastomeric small‐diameter vascular graft reinforced with a highly flexible Nitinol mesh. Issue 4 (3rd September 2018) - Soldani, Giorgio; Murzi, Michele; Faita, Francesco; Di Lascio, Nicole; Al Kayal, Tamer; Spanò, Raffaele; Canciani, Barbara; Losi, Paola
Abstract: Highly porous small‐diameter vascular grafts (SDVGs) prepared with elastomeric materials such as poly(ether urethane) (PEtU)–polydimethylsiloxane (PEtU‐PDMS) are capable to biodegrade but may develop aneurismal dilatation. Through a compliance/patency assessment with ultrasound techniques, the current study investigated the functionality, in terms of patency and endothelialization, of a highly flexible and porous Nitinol mesh incorporated into PEtU‐PDMS SDVGs in a sheep carotid model. Nitinol‐PEtU‐PDMS grafts with an internal diameter (ID) of 4 mm were manufactured by spray, phase‐inversion technique. Compliance tests were performed by ultrasound (US) imaging using a high‐resolution ultrasound diagnostic system. Ten adult sheep were implanted with 7 cm long grafts. The results of this study demonstrated an almost complete neointima luminal coverage in transmurally porous grafts reinforced with the Nitinol meshes after 6 months of implantation. Additionally, ultrasound has been used to quantitatively assess and monitor hemodynamic variables in an experimental model of synthetic vascular graft replacement. The use of reinforced PEtU‐PDMS grafts may accelerate the endothelialization process of relatively long grafts, such as those needed for aortocoronary bypass. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 951–964, 2019.